مقاصد الشريعة ونظام الصيرفة عبر الإنترنت: آثارهما في تقديم الخدمات = Maqāṣid al-Sharīʿah and the online banking system: implications for service delivery - Bello, Nabil; Haque, Must. Fahinur; Adeyemi, Adewale Abideen; Hasan, Aznan (Department of Fiqh and Usul Fiqh, Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
One of the Sharīʿah’s requirements in conducting transactions is realising the Maqāṣid al-Sharīʿah. The Modern online banking system is very common to everyone, so it is considered as al-ʿUrf or al-ʿādah (common practice or custom) under the Sharīʿah. However, its practice is surrounded with security concerns, ease of use, and trust and cost implications that need observance of some Sharīʿah rulings. This qualitative analytic study uses the framework for the Maqāṣid al-Sharīʿah to explicate the ideal practice of online banking in service delivery to realize the Maqāṣid al-Sharīʿah. While Islam places more attention on the essential needs, online banking should as well be intended to provide essential services to customers and remove hardship in financial transactions. Banks should hence desist from causing any harm through the charging of hidden fees, causing more confusion to their clients, and even devising deceptive means that lead to the charging of ribā. Instead, banks should use online services to introduce means that promote the realization of the Maqāṣid al-Sharīʿah. This paper stresses the importance of financial technology in realising the Maqāṣid al-Sharīʿah.